Efficacy of diclazuril and toltrazuril in the prevention of coccidiosis in dairy calves under field conditions. (31st January 2015) - Zechner, G.; Bauer, C.; Jacobs, J.; Goossens, L.; Vertenten, G.; Taylor, M. A.
Abstract : A blinded, controlled, randomised field study was undertaken on two commercial dairy farms in Germany to compare the efficacy of the anticoccidials, diclazuril and toltrazuril in the prevention of bovine coccidiosis. A total of 86 calves aged between five and six weeks were randomly allocated to two treatment and one untreated control groups. Calves were monitored for 78 days post‐treatment by clinical observation, bodyweight gain, faecal oocyst counts (FOCs) and coccidia species differentiation. Strategic treatments had no significant effect on bodyweight gains (P>0.05). Whilst the number of diarrhoea days was similar for all three groups from days 1 to 41, there was a significant difference in the number and percentage of diarrhoea days from day 42 with the diclazuril‐treated group showing only one diarrhoea day compared with 9 days (P=0.0195) and 18 days (P=0.0027) for the control and toltrazuril‐treated groups, respectively. FOCs in control calves fluctuated throughout the period of study indicating continued coccidia challenge. FOCs in the diclazuril‐treated calves declined to low levels post‐treatment, increasing to occasional counts >500 oocysts per gram of faeces (OPG) between days 27 and 42, but thereafter remained low. Calves treated with toltrazuril also showed low FOCs until day 40 but then showed several peaks of oocyst output >500 OPG coinciding with days of diarrhoea.